SARS-CoV-2 Spike Protein and Long COVID—Part 1: Impact of Spike Protein in Pathophysiological Mechanisms of Long COVID Syndrome - Bruno Pereira de Melo; Jhéssica Adriane Mello da Silva; Mariana Alves Rodrigues; Julys da Fonseca Palmeira; Felipe Saldanha-Araujo; Gustavo Adolfo Argañaraz; Enrique Roberto Argañaraz (Viruses)
SARS-CoV-2 infection has resulted in more than 700 million cases and nearly 7 million deaths worldwide. Although vaccination efforts have effectively reduced mortality and transmission rates, a significant proportion of recovered patients—up to 40%—develop long COVID syndrome (LC) or post-acute sequelae of COVID-19 infection (PASC). LC is characterized by the persistence or emergence of new symptoms following initial SARS-CoV-2 infection, affecting the cardiovascular, neurological, respiratory, gastrointestinal, reproductive, and immune systems. Despite the broad range of clinical symptoms that have been described, the risk factors and pathogenic mechanisms behind LC remain unclear. This review, the first of a two-part series, is distinguished by the discussion of the role of the SARS-CoV-2 spike protein in the primary mechanisms underlying the pathophysiology of LC.